On the Achievable Rate of Stationary Fading Channels - Dörpinghaus, Meik (Foundations in Signal Processing, Communications and Networking, 2011)
Virtually all mobile communications systems face the problem that transmission takes place over a time-varying fading channel whose realization is unknown to the receiver. For the design of communication systems it is important to know performance limits for communication over such channels. Therefore, the present book discusses various aspects regarding the capacity/achievable data rate of stationary fading channels. In this regard, it spans a wide range from bounds on the capacity/achievable rate for such channels to a study of the achievable rate with practical receivers. It reveals in detail which portion of the mutual information between the transmitter and the receiver can be retrieved in practice by synchronized detection. In this context, the book covers: - A study of the achievable rate of stationary Rayleigh fading channels, mainly focusing on i.i.d. Gaussian input symbols, including multiple-input multiple-output and frequency-selective channels. - An examination of the achievable rate with practical systems relying on pilot symbols, including conventional receivers using synchronized detection with a solely pilot based channel estimation, enhanced receivers using code-aided channel estimation, and a comparison to the achievable rate with optimal joint processing of pilot and data symbols. - An investigation of optimal discrete input distributions, showing that periodic pilot symbols as used in practice are not capacity-achieving in general. However, they allow for receiver implementations with reasonable complexity while showing only a small decrease in performance.